The Panama Papers in New Zealand media: A modern diachronic corpus assisted discourse study. (August 2018) - Owen, Thomas; Annabell, Taylor
Highlights: The initial data releases in April and May 2016 acted as news pegs. Reporting was restricted to the events of the leaks, with no ongoing influence on tax news discourse. Coverage was characterized by a tension between global and national sensibilities.